1979
DOI: 10.2134/agronj1979.00021962007100010005x
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Application of P. II. Yield Responses of Corn and Soybeans Sprayed with Various Condensed Phosphates and P‐N Compounds in Greenhouse and Field Experiments1

Abstract: Greenhouse and field experiments were conducted with corn (Zea mays L.) and soybeans (Glycine max L. Merr.) to evaluate the growth response of foliar sprays with several condensed phosphates and P‐N compounds. The maximum concentration of P tolerated in solutions of tri‐ and tetrapolyphosphates applied as sprays in the greenhouse was 1.3% with corn and 1.1% with soybeans. The maximum concentration of P tolerated as orthophosphate was 0.5% with corn and 0.4% with soybeans. With soybeans, the yields of plants sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…The appearance of leaf burn where foliar droplets have been applied has been observed in many studies (Barel and Black 1979b;Parker and Boswell 1980) and generally is not detrimental to the plant. However, some studies have resulted in leaf burn so severe that part or all of the leaf dies, causing a lower yield for foliar-applied treatments.…”
Section: Phosphorus Rate and Foliar Scorchmentioning
confidence: 93%
See 3 more Smart Citations
“…The appearance of leaf burn where foliar droplets have been applied has been observed in many studies (Barel and Black 1979b;Parker and Boswell 1980) and generally is not detrimental to the plant. However, some studies have resulted in leaf burn so severe that part or all of the leaf dies, causing a lower yield for foliar-applied treatments.…”
Section: Phosphorus Rate and Foliar Scorchmentioning
confidence: 93%
“…Foliar applications of P have been tested on various agricultural crops such as soybeans (Garcia and Hanway 1976;Barel and Black 1979b;Syverud et al 1980;Mallarino et al 2001Mallarino et al , 2005, clover (Bouma 1969, Bouma andDowling 1976), wheat (Arif et al 2006;Mosali et al 2006) and corn (Harder et al 1982;Giskin and Efron 1986;Girma et al 2007). The objectives of such studies have been to identify the best formulation, rate, timing, crop type and sites.…”
Section: Plant Studies With Foliar P Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Harder, Carlson, and Shaw (1982) found that foliar fertilizer applied after silking did not translate into increased grain yield. On the other hand, Barel and Black (1979b) reported an increased grain yield due to foliar P compared with control (untreated check).…”
Section: Grain and Forage Yieldsmentioning
confidence: 90%